Reagan and the States. - Nathan, Richard P. (Princeton University Press, 2014)
Here is the most thorough study to date on the impact of Ronald Reagan's policies on the states, especially the outcomes of his well-known budget cuts. A treasure trove of information that will be essential for interpretations of the Reagan presidency. Originally published in 1987. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in dur.
Keywords: Budget -- United States.; Grants-in-aid -- United States.; Intergovernmental fiscal relations -- United States.; Finance, Public -- United States -- States -- Case studies.; Local finance -- United States -- Case studies.; United States -- Economic policy -- 1981-1993.; Subventions de l'État aux collectivités locales -- États-Unis.; Finances publiques -- États-Unis -- États -- Études de cas.; Finances locales -- États-Unis -- Études de cas.; États-Unis -- Politique économique -- 1981-1993.; POLITICAL SCIENCE -- American Government -- General.; Budget; Economic policy; Finance, Public -- U.S. states; Grants-in-aid; Intergovernmental fiscal relations; Local finance; United States; 1981-1993; Case studies